KOMPONEN EVALUASI PEMBELAJARAN BIDANG STUDI PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI - Akhmad Syahid (IAI Al-Mawaddah Warrahmah Kolaka, 2018)
Evaluation of learning Islamic Religious Education and Character Budi is an important part in measuring the achievement of learning in the field of study. The evaluation component compiled reflects the comprehensive evaluation in a field of study. Evaluation of learning not only measures the learning outcomes achieved by learners, but measures the overall set of learning done by a teacher. The series of learning in question is started from the planning, then the implementation, and the last reporting. Therefore the study of this subject is the evaluation of the whole series of learning with four main components namely planning, learning activities, professional development, and learning outcomes. Learning Planning Components include assessment of learning resources. Components of learning implementation include assessments of principals, assessments of learners, and self-assessment. The professional development component includes all activities that teachers follow to improve their competence. Learning result components include analysis of learning outcomes.